2019
DOI: 10.1038/s42003-019-0626-9
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal mistranslation leads to silencing of the unfolded protein response and increased mitochondrial biogenesis

Abstract: Translation fidelity is the limiting factor in the accuracy of gene expression. With an estimated frequency of 10−4, errors in mRNA decoding occur in a mostly stochastic manner. Little is known about the response of higher eukaryotes to chronic loss of ribosomal accuracy as per an increase in the random error rate of mRNA decoding. Here, we present a global and comprehensive picture of the cellular changes in response to translational accuracy in mammalian ribosomes impaired by genetic manipulation. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 73 publications
3
39
0
Order By: Relevance
“…The protein product of 12 of the genes having negative interactions with AZC either form the proteasome or are involved in the assembly of the proteasome (UBP6, RPT6, RPN11, PUP2, POC4, PRE6, PBA1, RPN11, PRE4, IRC25, RPN12, PRE9). This supports previous reports demonstrating the requirement for proteasomal protein degradation for cells to cope with proteotoxic stress (Ruan et al 2008;Hoffman et al 2017;Shcherbakov et al 2019). Consistent with this, the gene encoding ubiquitin (UBI4), a post-translational modification required in protein degradation signaling, also has a negative synthetic interaction with AZC and thialysine.…”
Section: The Proteasome Is Required To Cope With Proteotoxic Stress Csupporting
confidence: 90%
“…The protein product of 12 of the genes having negative interactions with AZC either form the proteasome or are involved in the assembly of the proteasome (UBP6, RPT6, RPN11, PUP2, POC4, PRE6, PBA1, RPN11, PRE4, IRC25, RPN12, PRE9). This supports previous reports demonstrating the requirement for proteasomal protein degradation for cells to cope with proteotoxic stress (Ruan et al 2008;Hoffman et al 2017;Shcherbakov et al 2019). Consistent with this, the gene encoding ubiquitin (UBI4), a post-translational modification required in protein degradation signaling, also has a negative synthetic interaction with AZC and thialysine.…”
Section: The Proteasome Is Required To Cope With Proteotoxic Stress Csupporting
confidence: 90%
“…Analysis also revealed prominent protein degradation mechanisms including ER oxidant stress pathways including iNOS signaling (9/35 genes), the protein ubiquitination pathway (38/172 genes), and mitochondria-mediated cell death pathways (27/396 genes). In addition, mitochondrial biogenesis and mTOR have been directly linked to proteotoxicity and the UPR 35,36 . Taken together, these analyses suggest that the CORE and UPR mediate gentamicin-induced proximal tubule cell injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our shRNA screen, genes that alter survival in gentamicin-exposed human renal cells have been directly or indirectly linked to proteotoxicity and UPR. Specifically, EIF2, PTEN, mitochondrial biogenesis, and mTOR have been directly implicated in the UPR 35,36,63,66 , whereas oxidative stress has been linked to iNOS, intrinsic antioxidants, and P53 67 . In addition to these screening results and the evidence of reduced chaperone function in gentamicin-exposed cells, chaperones are an ideal therapeutic target due to their potential protective effects on both CORE and UPR pathways, and robust inducibility by GGA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to cytosolic chaperones and the proteasome also mitochondria appear to play a crucial role in the maintenance of proteostasis ( 91 , 92 ). Cytosolic aggregating proteins were shown to stimulate mitochondrial biogenesis and are imported into mitochondria for subsequent degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic aggregating proteins were shown to stimulate mitochondrial biogenesis and are imported into mitochondria for subsequent degradation. It was suggested that aggregate overload may damage mitochondrial function and that reduced mitochondrial activity impairs cytosolic proteostasis ( 91 ). Hence, the induced expression of genes related to mitochondria function in the aggregation prone tRNA modification mutants and impaired respiratory growth could be linked to mitochondrial aggregate overload.…”
Section: Discussionmentioning
confidence: 99%